Internet for library and information service professionals - Dawson, Andy (Aslib LondonGB, 1995)
Looks at aspects such as the nature of the Internet; Email, lists and newsgroups; telnet, hytelnet and remote login; FTP and Archie; Gopher and Veronica; WAIS; and, the World Wide Web.